DESENTRALISASI PENDIDIKAN (SEBAGI UPAYA PEMERATAAN PENDIDIKAN) - Arif Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2016)
Reformation brought changes in all fields one of which is regional autonomy. The implementation of regional autonomy with dsentrealisari base is constituted by the desire to create a democracy, equity, and efficiency. Decentralization policy implications bangs must come from the grassroots to the top, no longer from top to bottom. The reality in the field of education does not seem to go according to the circumstances. Policies that exist at this time impressed derived and compiled directly by the Department of education regardless of the participation of the community. Though education is supposed to be centered in the community, should be for the people, so it shall be guided by the people. Openness and opportunity for bertpartisipasi in the field of education should be put to good use in a way that every government should implement a policy botom-up system, that is, policies that come from the community conditions (bottom to top). From the above analysis, the findings in this paper I will present the material Education Decentralization in Indonesia.